Endocrine Delivery System of NK4, an HGF-Antagonist and Anti-Angiogenic Regulator, for Inhibitions of Tumor Growth, Invasion and Metastasis - Mizuno, Shinya; Nakamura, Toshikazu (IntechOpen, 2011)
None